THE INFLUENCE OF CULTURAL FACTORS, SOCIAL FACTORS AND PERSONAL FACTORS ON THE DECISION TO USE FAKHIRAMAKE UP WEDDING SERVICES IN BIREUN DISTRICT - Subhan, M.; Zainura, Zainura (Berajah Journal, 2024)
This study aims to analyze the influence of Cultural Factors, Social Factors, and Personal Factors on the purchasing decisions of Wedding Fakhira Make Up services in Bireuen Regency. Data for this research were collected from 100 respondents and analyzed using the SPSS (Statistical Package for the Social Sciences) software. The results of the study indicate that cultural factors have a positive and significant impact on the purchasing decisions of Fakhira Make Up wedding services in Bireuen Regency. This suggests that an increase in cultural factors leads to an increase in consumer purchasing decisions. Social factors also have a positive and significant influence on purchasing decisions, indicating that an increase in social factors leads to an increase in consumer purchasing decisions. Similarly, personal factors have a positive and significant impact on purchasing decisions, indicating that an increase in personal factors leads to an increase in consumer purchasing decisions.